2010
DOI: 10.1080/00207144.2011.522874
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low-Back Pain Modulation Is Enhanced by Hypnotic Analgesic Suggestion by Recruiting an Emotional Network:A PET Imaging Study

Abstract: This study aimed to characterize the neural networks involved in patients with chronic low-back pain during hypnoanalgesia. PET was performed in 2 states of consciousness, normal alertness and hypnosis. Two groups of patients received direct or indirect analgesic suggestion. The normal alertness state showed activations in a cognitive-sensory pain modulation network, including frontotemporal cortex, insula, somatosensory cortex, and cerebellum. The hypnotic state activated an emotional pain modulation network,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 33 publications
(44 reference statements)
2
30
1
Order By: Relevance
“…These studies have concluded that hypnosis can impact pain by affecting a number of different neurophysiological processes that make up the pain matrix, rather than by influencing a single mechanism or process. Specifically, research indicates that hypnosis can impact activity in: (1) the periphery and spinal cord [67][68][69], (2) the thalamus [65,70,71], (3) the sensory cortices [72,73], (4) the insula [70,71,73], (5) the ACC [35,70,71,[73][74][75], and (6) the prefrontal cortex [70,71,73,76]. Given the extensiveness of these previous reviews, this section will briefly review past research that has examined the neurophysiological effects of hypnotic analgesia, specifically focused on the role of suggestion type [35,72,77].…”
Section: Neurophysiological Effects Of Hypnosismentioning
confidence: 99%
See 3 more Smart Citations
“…These studies have concluded that hypnosis can impact pain by affecting a number of different neurophysiological processes that make up the pain matrix, rather than by influencing a single mechanism or process. Specifically, research indicates that hypnosis can impact activity in: (1) the periphery and spinal cord [67][68][69], (2) the thalamus [65,70,71], (3) the sensory cortices [72,73], (4) the insula [70,71,73], (5) the ACC [35,70,71,[73][74][75], and (6) the prefrontal cortex [70,71,73,76]. Given the extensiveness of these previous reviews, this section will briefly review past research that has examined the neurophysiological effects of hypnotic analgesia, specifically focused on the role of suggestion type [35,72,77].…”
Section: Neurophysiological Effects Of Hypnosismentioning
confidence: 99%
“…Given the extensiveness of these previous reviews, this section will briefly review past research that has examined the neurophysiological effects of hypnotic analgesia, specifically focused on the role of suggestion type [35,72,77]. Additionally, three studies that were not included in these previous reviews will be discussed, including one recent study evaluating the neurophysiological mechanisms associated with hypnotic induction and two studies that studied the neural processes correlated with suggestions [73,76,78].…”
Section: Neurophysiological Effects Of Hypnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with local anesthesia, beneficial effects of hypnosis on patients undergoing surgery have been previously described [8,9]. From an Ericksonian perspective "indirect" suggestions are theoretically approached as suggestions which can circumvent the censorship of consciousness to reach the "unconscious" where they can activate dormant potentials [8,10].…”
Section: Case Reportmentioning
confidence: 99%